Design Pembelajaran Berpihak pada Peserta Didik terhadap Hasil Belajar Materi Pecahan Senilai Kelas IV SD Negeri Tambakrejo 01 - Istiana Wijayanti; Ida Dwijayanti; Arum Asmawati (Journal on Education, 2025)
Student-centered learning has not been successfully implemented, according to the findings of interviews conducted with fourth grade teachers. Students have a variety of learning demands. Efforts made by teachers by using TaRL techniques to increase students' interest in learning. Finding out what the value of fractions is through various methods is the goal of the PBL learning paradigm. This research uses mixed methodology, which combines two different approaches: qualitative and quantitative with a case study research design. By thoroughly describing a case that becomes the focal point of the research. The data collection method in this study is based on the assessment of learning outcomes, which includes knowledge, understanding, ability, attitude, and value. Students' learning outcomes were maximized in the first lesson using the TaRL approach. This method makes learning more focused and efficient. Although the TaRL approach can be used to improve student learning outcomes, it still requires hard work and creativity to advance students who have not achieved their learning outcome targets and retain students who have achieved their learning outcome targets.